PSYCHOLOGICAL MECHANISMS OF UNDERSTANDING HUMAN NATURE IN PSYCHOANALYSIS - Boronova Hilola Akramjonovna (Galaxy International Interdisciplinary Research Journal, 2023)
Counseling is an interpersonal process. In the process of consultation, an environment of trust is created between the consultant and the client for the psychologist and the client to understand each other and for the client to change and grow. In any consultation, there are four variables that determine the change of the client: the psychologist, the client, the environment in which the consultation is held, and the theoretical orientation of the consulting psychologist. Most approaches to counseling fall into one of four theoretical categories: psychoanalytic, affective, cognitive, and behavioral. The article talks about the methodological foundations of the psychoanalytic approach.